(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2025)
This article discusses the translation and significance of medical terms and phrases used in English. It provides information on the structural and morphological significance of English medical terms, their role in medicine and their specific features. In addition, the specific role and models of English phrases used in communicative communication in medicine are presented based on examples and analysis.